Investigation of novel functions of a gap junction protein, connexin46 - Banerjee, Debarshi (Kansas State University, 2010)
Connexin proteins are the principle structural components of gap junction channels that connect the cytoplasm of two cells and maintain direct intercellular communication through the exchange of ions, small molecules and cellular metabolites. Colocalization and tissue-specific expression of diverse connexin molecules are reported to occur in a variety of organs. Impairment of gap junctional intercellular communication, caused by mutations, gain of function or loss of function of connexins, is involved in a number of diseases including the development of cancer. Here the functions of a gap junction protein, connexin46 (Cx46), have been investigated in two hypoxic tissues, lens and breast tumor. We show that human breast cancer cells, MCF-7 and breast tumor tissues express connexin46 (Cx46) and it plays a critical role in protecting cells against hypoxia-induced death. Interestingly, I find that Cx46 is upregulated in MCF-7 breast cancer cells and human breast cancer tumors. Downregulation of Cx46 by siRNA promotes cell death of human lens epithelial cells (HLEC) and MCF-7 cells under hypoxic conditions. Furthermore, direct injection of anti-Cx46 siRNA into xenograft tumors prevents tumor growth in nude mice. Our result suggests that both normal hypoxic tissue (lens) and adaptive hypoxic tissue (breast tumor) utilize the same protein, Cx46, as a protective strategy against hypoxia. In the last part of the dissertation, we show that over expression of Cx46 induces the degradation of another connexin, connexin43, in rabbit lens epithelial NN1003A cells. Over expression of Cx46 increases ubiquitination of Cx43. Moreover, the Cx46-induced Cx43 degradation is counteracted by inhibitors of proteasome. Taken together, these data indicate that the degradation of Cx43, upon Cx46 over expression, is mediated by the ubiquitin-proteasome pathway. I also provide evidence that that C-terminal tail of Cx46 is essential to induce degradation of Cx43. Therefore, our study shows that Cx46 has a novel function in the regulation of Cx43 turnover in addition to its conventional role as a gap junction protein. This may contribute to protection from hypoxia in both the lens and tumors.
Keywords: gap junctions; connexin46; connexin43; breast tumor; lens; hypoxia; Biology, Cell (0379)